2011
DOI: 10.2337/db11-0549
|View full text |Cite|
|
Sign up to set email alerts
|

TRB3 Gene Silencing Alleviates Diabetic Cardiomyopathy in a Type 2 Diabetic Rat Model

Abstract: OBJECTIVETribbles 3 (TRB3) is associated with insulin resistance, an important trigger in the development of diabetic cardiomyopathy (DCM). We sought to determine whether TRB3 plays a major role in modulating DCM and the mechanisms involved.RESEARCH DESIGN AND METHODSThe type 2 diabetic rat model was induced by high-fat diet and low-dose streptozotocin. We evaluated the characteristics of type 2 DCM by serial echocardiography and metabolite tests, Western blot analysis for TRB3 expression, and histopathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 37 publications
12
124
1
1
Order By: Relevance
“…It reversed the altered blood glucose, HbA 1 and lipid levels, and plasma GLP-1 and insulin levels, and reduced fat deposition in diabetic myocardial and epicardial tissues, so sitagliptin may play an essential role in improving diabetic cardiac dysfunction and cardiomyopathy. Inflammation is a key pathophysiologic factor in diabetic cardiomyopathy (1,2,16,21), and is closely related to fat deposition. Ti et al (16) reported that TNF-a and IL-6 were overexpressed in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It reversed the altered blood glucose, HbA 1 and lipid levels, and plasma GLP-1 and insulin levels, and reduced fat deposition in diabetic myocardial and epicardial tissues, so sitagliptin may play an essential role in improving diabetic cardiac dysfunction and cardiomyopathy. Inflammation is a key pathophysiologic factor in diabetic cardiomyopathy (1,2,16,21), and is closely related to fat deposition. Ti et al (16) reported that TNF-a and IL-6 were overexpressed in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a key pathophysiologic factor in diabetic cardiomyopathy (1,2,16,21), and is closely related to fat deposition. Ti et al (16) reported that TNF-a and IL-6 were overexpressed in diabetic rats. Biomarkers of inflammation including TNF-a and IL-6 levels are associated with risk of developing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, improvements in diabetic cardiomyopathy and atherosclerosis in type 2 diabetes could have been related to improved metabolic control. 61,62 mTOR is a conserved serine/threonine kinase modulated by growth factors and cellular energy status. It forms two distinct molecular complexes known as mTOR complex 1 (mTORC1) and mTORC2.…”
Section: Thr308mentioning
confidence: 99%